ANALYSIS OF EFFICIENCY OF VACCINES AGAINST BRUCELLOSIS IN CATTLE IN THE REPUBLIC OF KAZAKHSTAN - Abutalip, Aspen; Matikhan, Nurali; Kanatbayev, Serik; Bazarbayev, Marat; Vorobyov, Viktor (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This article analyzes the efficiency of live vaccines obtained from the strains of Brucella abortus 82 and 75/79-AV and RB-51 in some regions of Kazakhstan in 2012-2014 and recommends optimal scheme of their use. Methods: There were analyzed the effectiveness of the use of live vaccines (manufactured in Russia) obtained from strains of B. abortus 19, 82 and 75/79-AV in combination with post-vaccination diagnostics of brucellosis in cattle in the farmsteads owned by Vostok-moloko Corporation in Eastern Kazakhstan in the period of 2012-2015. Results: The results of these tests prove that studies of animals 1 month after the vaccination have helped to further identify the animals with hidden form of brucellosis provoked by R-vaccine, which explains the favorable outcome of the research. Conclusion: The above-described scheme of anti-brucellosis activities ensures effective control of the epizootic process of brucellosis by establishing permanentâ€ (continuous) immunity and permanent control of epizooty in brucellosis threatened/unsafe herds.